The Influence of Project Based Learning on Social Studies Content Understanding in the Merdeka Curriculum at SD 006 Langgini - Laspita, Romi; Haris, Hanisa; Nasrul, Nasrul; Rani, Afriza Rahma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aimed to determine the effect of Project-Based Learning on students’ understanding of Social Studies content within the Merdeka Curriculum at Elementary School 006 Langgini. This research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. The research sample consisted of 17 students selected through total sampling. The research instrument was a Social Studies comprehension test that had been tested for validity and reliability. Data were analyzed using descriptive statistics and a paired sample t-test. The results indicated an increase in the students’ average comprehension scores after the implementation of Project-Based Learning. Hypothesis testing revealed that Project-Based Learning had a significant effect on students’ understanding of Social Studies content in the Merdeka Curriculum at Elementary School 006 Langgini. Therefore, Project-Based Learning can be used as an alternative instructional strategy to enhance students’ conceptual understanding of Social Studies in elementary schools.